Propranolol As an Anxiolytic to Reduce the Use of Sedatives for Critically Ill Adults Receiving Mechanical Ventilation (PROACTIVE): An Open-Label Randomized Controlled Trial - Downar, James; Lapenskie, Julie; Kanji, Salmaan; Watpool, Irene; Haines, Jessica; Saeed, Uzma; Porteous, Rebecca; Polskaia, Nadia; Burry, Lisa; Himed, Shuhira; Anderson, Koby; Fox-Robichaud, Alison (Critical care medicine, 2025)
Surges in demand for sedatives for mechanical ventilation during the COVID-19 pandemic caused shortages of sedatives globally. Propranolol, a nonselective beta-adrenergic blocker, has been associated with reduced agitation and sedative needs in observational studies. We aimed to test whether propranolol could reduce the dose of sedatives needed in mechanically ventilated patients. Open-label randomized controlled trial. Three academic hospitals. Any nonparalyzed patient receiving mechanical ventilation and requiring high-dose sedatives. Enteral propranolol 20-60 mg every 6 hours titrated to effect in the intervention group; all participants received protocol-titrated sedation with propofol or midazolam. Mean change in 24 hours dose of sedative from baseline to day 3, proportion of sedation scores within target, and occurrence rate of adverse events. We enrolled a planned 72 patients between January 2021 and October 2022. Sixty-nine percent were male with a mean (sd) age of 54 years (15.91 yr). Most were admitted for COVID or non-COVID pneumonia. Intervention participants received propranolol for a mean of 10 days (mean daily dose, 90 mg). There was a significantly larger decrease in sedative dose from baseline (54% vs. 34%; p = 0.048) and more sedation assessments within target range (48% vs. 35%; p < 0.0001) in the intervention group compared with controls. There were no differences in mortality or adverse events. Propranolol is an inexpensive drug that effectively lowered the need for sedatives in critically ill patients managed in the COVID-19 pandemic. Propranolol may help preserve limited supplies of sedatives while achieving target sedation.